تمرينات اليوغا و تأثيرها على تطوير دافعية التعلم لدى طلبة كلية التربية الرياضية - علي، شيماء (جامعة القادسية - كلية التربية الرياضية, 2014)
تمركزت اهمية البحث في دور تمارين اليوغا في التأثير على الطالب وزيادة دافعية التعلم لهم فيما تمركزت مشكلة البحث في تأثير تمرينات اليوغا في تطوير دافعية التعلم للطالب ودورها الكبير في زيادة التعبئة النفسية وزيادة استرخاء الطالب وبالتالي تطوير الحالة النفسية للطلبة. هدفت الدراسة الى التعرف الى اعداد تمرينات خاصة باليوغا لطلبة كلية التربية الرياضية (المرحلة الثانية) جامعة بابل والتعرف على تأثير تلك التمارين على تطوير بعض القدرات الوظيفية والحركية الخاصة لدى لاعبات نادي فتاة بغداد في لعبة المبارزة. وقد تم استخدام المنهج التجريبي وذك لملائمته لحل مشكلة البحث على طلبة كلية التربية الرياضية / جامعة بابل (المرحلة الثانية) والبالغ عددهم (60) طالب. وقد استنتجت الباحثة بأن هناك تأثير ايجابي لتمرينات اليوغا على تطوير دافعية التعلم لدى طلبة المرحلة الثانية. إذا توصي الباحثة بضرورة استخدام برامج تتضمن تمرينات اليوغا واعطائها الدور والمكانة في الدروس العلمية لكلية التربية الرياضية وذلك لدورها الايجابي في تحسين وتطوير قابلية الطالب الذهنية وحصول الاسترخاء التام له. in the development of student learning motivation and its significant role in increasing the mobilization of mental relaxation and increase student and thus the development of the mental state of the students. The study aimed to identify exercises to prepare for a private yoga students of the Faculty of Physical Education (Phase II ), University of Babylon, and to identify the impact of these exercises to develop some functional capacity and motor own with the players club girl Baghdad in a game fencing . I have been using the experimental approach reminded suitability to solve the problem of the research on the students of the Faculty of Physical Education / University of Babylon (Phase II) and totaling 60 students. The researcher concluded that there is a positive effect of yoga exercises on the development of learning motivation among the students of the second phase . The researcher recommends the use of programs include yoga exercises and give it a role and prestige in the scientific lessons of the Faculty of Physical Education and to its positive role in the improvement and development of student's mental ability and get fully relax him .
Keywords: اليوغا -- دافعية التعلم -- التربية الرياضية -- طلاب التربية الرياضية